An evaluation of the adoption of ITIL (IT Infrastructure Library) Framework and its Implication on the Delivery of IT Services of Selected BPO and Contact Centers in the Philippines - Tiambeng, Ken Arthur; Imbang, Glen (Quezon City University of the Philippines Diliman, 2009)
The project involves an analysis of the present capability of selected Business Process Outsourcing and Contact Centers in delivering its services, and the possible implications of the adoption of ITIL. The study showed that firms which adopted ITIL as a framework were able to improve their processes, which resulted to improvement in the delivery of services. In the Philippines, there are only a few of these organizations which have adopted ITIL as an IT framework for their organization. And for these organizations, only selected disciplines were adopted and not the entire framework. This was due to applicability to the organization and due to cost and resources needed to implement. There is a lack of awareness and education in the country for this framework. The study showed there are very limited education and training centers for ITIL, and that the cost is a factor for certification exam of an individual. ITIL should be adopted by BPO and Contact Centers in order to improve and standardize their delivery of service to their clients. ITIL could also deliver considerable cost reduction opportunities by streamlining processes. Since the framework is widely adopted in Europe and other Asian countries in the BPO and Contact Center industry, it is recommended that academe specializing in the technology service industry should adopt ITIL into their curriculum. The CICT (Commission on Information Communication Technology) should also help develop the human capital through education and training in service management in the Philippine BPO/CC industry; since this is a factor looked at by foreign investors.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Call centers -- Philippines; ITIL (IT Infrastructure Library).; Business process outsourcing (BPO).